2012
DOI: 10.1590/s1516-05722012000400010
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial citotóxico e genotóxico de Plantago major L. em sistemas teste in vivo

Abstract: RESUMO:A infusão das folhas de Plantago major (Plantaginaceae), conhecida como tansagem ou transagem, é usada como antibiótica, antiinflamatória, anti-séptica, anti-térmica, na prevenção de tumores e no tratamento de neoplasias. Este efeito é atribuído aos flavonóides encontrados em diversas espécies do gênero Plantago. O presente estudo objetivou avaliar os potenciais efeitos, tóxico e mutagênico, do extrato bruto hidroalcoólico de folhas de P. major, por meio dos testes in vivo de Allium cepa e do micronúcle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
(11 reference statements)
0
5
0
7
Order By: Relevance
“…This in vitro test is very useful as a first-tier analysis of cytotoxicity and genotoxicity, because of the simplicity, low relative cost, versatility and minimum laboratory facilities required for its performance (Khora et al, 1997). Moreover, the results obtained using the A. cepa root model show a high degree of conformity with the results obtained from mammalian assays (Luz et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This in vitro test is very useful as a first-tier analysis of cytotoxicity and genotoxicity, because of the simplicity, low relative cost, versatility and minimum laboratory facilities required for its performance (Khora et al, 1997). Moreover, the results obtained using the A. cepa root model show a high degree of conformity with the results obtained from mammalian assays (Luz et al, 2012).…”
Section: Introductionmentioning
confidence: 76%
“…Despite the therapeutic advantages of medicinal plants, their potential toxicity has not been recognized by the general public or by professional groups of traditional medicine (Soetan and Aiyelaagbe, 2009), and many plant species commonly considered medicinal can contain potentially dangerous substances (Rodrigues et al, 2011). Recent research studies conducted in vitro and in vivo assay have revealed that many plants used as food or in traditional medicine have cytotoxic and genotoxic effects (Sehgal et al, 2006;Dalla Nora et al, 2010;Luz et al, 2012;Ping et al, 2012). Therefore, evaluating the toxicological effects of any herbal extract intended to be used in humans is of utmost importance.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were found by Fachinetto and Tedesco (2009) on Allium cepa in the evaluation of the possible cytotoxic and genotoxic effect of aqueous extracts of Baccharis trimera and Baccharis articulata. Similarly, Luz et al (2012) concluded that foliar extracts of Plantago major cause alteration in the cell cycle, by inhibiting the division of the A. cepa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Os extratos da planta mais comumente estudados em relação a ação antimicrobiana e antibiofilme são os extratos hidroalcoólicos (Buffon et al, 2001;Freitas et al, 2002;Holetz et al, 2002;Cordeiro et al, 2006;Luz et al, 2012;Shirley et al,2015;Sharma et al,2016;Trindade et al;2019) Research, Society and Development, v. 9, n. 9, e496997495, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7495 10 que utilizou o extrato etanólico, porém discordando de outros artigos referentes ao extrato hidroalcóolico (Holetz et al, 2002;Trindade et al, 2019). Assim, o extrato etanólico apresentou um bom resultado para P. aeruginosa, diferindo dos resultados do extrato hidroalcóolico da Plantago major sobre a temática.…”
Section: Discussionunclassified